Whose privilege is it anyway?. Issue 10 (6th December 2019) - Morrison, Matthew
Abstract: The £10 subject access request served by Ashley Dawson-Damer on Taylor Wessing LLP (TW) in August 2014 has already resulted in two substantial hearings in the Chancery Division 1, and a two-day trip to the Court of Appeal. It is understood that the case is headed back to the Court of Appeal and that the appeal will be heard at some point in the new year.